Demonstration of tissue and peripheral blood eosinophils in patients with acute appendicitis - Shahla J. Hussein; Sarmad Raheem Kareem (Zanco Journal of Pure and Applied Sciences, 2023)
Acute appendicitis (AA) is the most surgical emergencies. Clinical diagnosis is usually confirmed by adjuvant laboratory testing but histopathology is the gold standard for diagnosis. Acute eosinophilic appendicitis (AEA) is a rare form of appendicitis with muscularis propria infiltration and muscle fiber edema. This study was aimed to find simple and accurate way for the diagnosis of unusual eosinophilic appendicitis that may requires postoperative special treatment. A prospective investigation was conducted at Shahid Dr. Khalid Teaching Hospital in (Koya city/ Kurdistan Region/ Iraq), This involves randomly selecting fifty appendectomy samples from emergency department patients from November 2021 to May 2022. Acute appendicitis is suspected in these patients based on their medical history, physical examination, investigation, and abdominal ultrasound. The patients were 28 (56% males) and 22 (44% females). Patients ranged in age from 4 to 43 years, with a mean of 20.98 years, and The majority of cases (60%) are under 20. A significant gradual (increase in weight and decrease in dimensions) of appendix with different age group was seen. Theoretical and actual means of CBC parameters differed significantly, although there was no significant sex difference. Tissue and peripheral blood eosinophil counts were directly correlated (P < 0.01), although there was a negative correlation between tissue and WBC count (P<0.0019). Congo red was statistically highly significant (P< 0.0001) in detecting tissue eosinophils compared to MGG and H&E. In conclusion, Congo red better than H&E and MGG staining for identifying tissue eosinophils, also tissue and peripheral blood eosinophils were positively correlated.